POST HARVEST TREATMENT OF PEST AFFECTING WHEAT GRAIN USING SOME SPICES (Pipernigrum, Zingiber Officinale AND Ellectaria cardamom). - Sulaiman, Bello; Mustafa, S. Y.; Allahnana, M. H.; Chigozie, L. A. (FUDMA JOURNAL OF SCIENCES, 2021)
The study was conducted in the Laboratory of Plant Science and Biotechnology Department, Federal University of Lafia, Nasarawa State to investigate the insecticidal potency of three spices powder namely black pepper (Piper nigrum L.), ginger (Zingiber officinale L.), and true green (Ellectaria cardamom L.), against wheat weevil (Tribolium castaneum) on stored wheat grain. Spices powder was added separately to 20g of wheat grain in plastic containers at four dosages 0.15, 0.27, 0.37, and 0.5% (w/w) while control had no spices powder. Twenty insect pests (Tribolium castaneum) were introduced into each container. Mortality counted in each treatment was recorded after 7, 14, 21, 28 and 35 days. All treatments were replicated three times. Variations were significantly observed in the overall effect of different plant powders on the mortality of weevils extracted from wheat kernel. Weevils treated with Piper nigrum powder exhibited the highest mean mortality (16.37), followed by Ellectaria cardamom (16.05) and lastly Zingiber officinale (13.82). from the result obtained, it is evident that the spice powders possessed insecticidal properties which if fully extracted could be used in post harvest treatment of wheat grain on storage